2018
DOI: 10.22616/erdev2018.17.n423
|View full text |Cite
|
Sign up to set email alerts
|

Process of matching work items between bim model and cost estimating software

Abstract: Abstract. This article is focused on the process of matching work items into an organized structure in order to semi-automatically identify work items and link them between BIModel and cost estimating software. Several sources are suggesting a computer aided cost estimation based on historical cost data, which is a desired method of cost estimation. However, it is only achievable, if cost data are collected in an organized way and if format of cost data is structured according with defined standards. Those sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Some articles also deal with the topic of "5D" on general level (like [9], in context of quantity surveying) or in context of different project phases (like [10], dealing with architectural study), but they were not useful for the purpose of this research. Some articles deal with the systematic approach for using BIM in specific cost related processes ( [11] in terms of process modelling, [12] in terms of LCC), but such papers do not deal with the topic of value estimation of existing buildings in the operational phase of the project.…”
Section: Methodsmentioning
confidence: 99%
“…Some articles also deal with the topic of "5D" on general level (like [9], in context of quantity surveying) or in context of different project phases (like [10], dealing with architectural study), but they were not useful for the purpose of this research. Some articles deal with the systematic approach for using BIM in specific cost related processes ( [11] in terms of process modelling, [12] in terms of LCC), but such papers do not deal with the topic of value estimation of existing buildings in the operational phase of the project.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Eastman, Eastman, Teicholz, Sacks and Liston [25] stress the significance of BIM in fostering effective communication among project participants. Stransky and Dlask [63] believe that BIM can serve as a decision-making tool during project implementation, leading to better performance. The literature highlights the importance of BIM in facilitating contracts' intelligent automation and promoting collaboration among team members, as demonstrated by the studies conducted by [64,65].…”
Section: The Correlation Between the Implementation Of Bim On Ossmentioning
confidence: 99%
“…(2) process-digitalization-and economics-related; (3) sustainability-and efficiency-related; and (4) visualization-and productivity-related. Stransky and Dlask [67] suggested that BIM aids decision making during project execution and improves construction productivity. Similarly, Eastman, et al [55] asserted that BIM improves collaboration among project teams.…”
Section: Drivers Of Bimmentioning
confidence: 99%